P146 Prescribing respiratory medicines without making a diagnosis of Asthma in UK Primary Care. (12th November 2015) - Clayton, S; Carter, V; Lenney, W; Price, D; Small, I; Smith, J
Abstract : Introduction and objectives: Despite asthma being one of the most prevalent worldwide chronic diseases, there remains a wide variation in prevalence. 1 The United Kingdom's (UK) National Review of Asthma Deaths 2 suggests avoidable factors play a part in as many as three-quarters of cases of asthma death. There is need to highlight and address many aspects of asthma care including the variation in diagnosis across all ages to enable appropriate treatment and improve symptom control. Here we investigate the relationship between prescribing respiratory medications and making the diagnosis of asthma, in UK primary care. Methods: GP recorded data were collected from 72 UK general practices participating in the pilot British Lung Foundation asthma management program in 3 health authority areas, (two Clinical Commissioning Groups in England and one Health Board in Scotland). A retrospective analysis was undertaken of the Optimum Patient Care Research Database. This included data on child and adult patients (aged between 0 and 89) in receipt of asthma medication without a diagnosis of a chronic respiratory disease, classified by the absence of a QoF recorded asthma diagnosis. Asthma medications prescribed in the previous 12 months were identified (beta2-agonists, inhaled corticosteroids, cromones or montelukast). Results: 39, 124 patients received at least one respiratory medication in the 12 months prior to data collection. Of these, 9, 761 (25.0%) had no clinical diagnosis ever recorded for asthma or COPD. 3, 655 patients were prescribed 2 or more respiratory prescriptions without a coded respiratory disease and 982 patients had a lower respiratory tract infection recorded within the same period. Conclusion: These results raise concern about over and under-treatment of children and adults in whom no diagnosis of asthma or any other chronic respiratory disease has been made. It is important that future Primary Care studies highlight the importance of early accurate diagnosis before starting treatment. Also, we suggest the present UK national prevalence and morbidity data are likely to underestimate the total burden of asthma within the Primary Care setting. References: 1 The NHS Atlas of Variation in Healthcare for Respiratory Disease, 2012 2 The National Review of Asthma Deaths London, NRAD, 2014